The Locare workflow: representing neuroscience data locations as geometric objects in 3D brain atlases - Blixhavn, Camilla H.; Reiten, Ingrid; Kleven, Heidi; Øvsthus, Martin; Yates, Sharon C.; Schlegel, Ulrike; Puchades, Maja A.; Schmid, Oliver; Bjaalie, Jan G.; Bjerke, Ingvild E.; Leergaard, Trygve B. (Frontiers in Neuroinformatics, 2024)
Neuroscientists employ a range of methods and generate increasing amounts of data describing brain structure and function. The anatomical location from which observations or measurements originate represent a common context for data interpretation, and a starting point for identifying data of interest. However, the multimodality and abundance of brain data pose a challenge for efforts to organize, integrate, and analyze data based on anatomical locations. While structured metadata allow faceted data queries, different types of data are not easily represented in a standardized and machine-readable way that allow comparison, analysis, and queries related to anatomical relevance. To this end, three-dimensional (3D) digital brain atlases provide frameworks in which disparate multimodal and multilevel neuroscience data can be spatially represented. We propose to represent the locations of different neuroscience data as geometric objects in 3D brain atlases. Such geometric objects can be specified in a standardized file format and stored as location metadata for use with different computational tools. We here present the Locare workflow developed for defining the anatomical location of data elements from rodent brains as geometric objects. We demonstrate how the workflow can be used to define geometric objects representing multimodal and multilevel experimental neuroscience in rat or mouse brain atlases. We further propose a collection of JSON schemas (LocareJSON) for specifying geometric objects by atlas coordinates, suitable as a starting point for co-visualisation of different data in an anatomical context and for enabling spatial data queries.